Police and community in Chicago: a tale of three cities - Skogan, Wesley G. (Studies in crime and public policy, 2006)
Community policing -- Crime, police and the three Chicagos -- Reengineering the police -- Involving the community -- Representing the community -- Tackling neighborhood problems -- Trends in neighborhood problems -- Trends in crime and fear -- Police and the public -- How did Chicago do?